2005
DOI: 10.1091/mbc.e04-11-0960
|View full text |Cite
|
Sign up to set email alerts
|

PostprenylationCAAXProcessing Is Required for Proper Localization of Ras but Not Rho GTPases

Abstract: The CAAX motif at the C terminus of most monomeric GTPases is required for membrane targeting because it signals for a series of three posttranslational modifications that include isoprenylation, endoproteolytic release of the C-terminal-AAX amino acids, and carboxyl methylation of the newly exposed isoprenylcysteine. The individual contributions of these modifications to protein trafficking and function are unknown. To address this issue, we performed a series of experiments with mouse embryonic fibroblasts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
141
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(163 citation statements)
references
References 36 publications
17
141
2
2
Order By: Relevance
“…Methylation has been shown to play an important role in interactions of RhoA with other proteins. It has been demonstrated by us and others (10,(31)(32)(33)(34) that the methylation status of RhoA directly impacts the RhoA-RhoGDI interaction and that RhoGDI plays an important role in the regulation of Rho activity. We hypothesize that, by controlling the methylation of RhoA, CES1 may be involved in the down-regulation of RhoA activity.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation has been shown to play an important role in interactions of RhoA with other proteins. It has been demonstrated by us and others (10,(31)(32)(33)(34) that the methylation status of RhoA directly impacts the RhoA-RhoGDI interaction and that RhoGDI plays an important role in the regulation of Rho activity. We hypothesize that, by controlling the methylation of RhoA, CES1 may be involved in the down-regulation of RhoA activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that ICMTmediated methylation may be critical for the function of only farnesylated proteins, thus greatly reducing the number of targets for ICMT inhibitors (Michaelson et al, 2005). Finally, ICMT-mediated methylation is also needed for the function of a subset of Rab family small GTPases, regulators of vesicular trafficking (Leung et al, 2006), thus expanding the candidate targets for ICMT inhibitors beyond CAAX-terminating proteins.…”
Section: Inhibitors Of Rasmentioning
confidence: 99%
“…The well-known chemotherapeutic compound methotrexate (an antifolate that blocks thymidine synthesis, which is necessary for tumor growth) causes accumulation of S-adenosylhomocysteine, a potent inhibitor of nearly all cellular methyltransferases; it has been suggested that at least some of methotrexate's antitumor activity may stem from its ability to inhibit Icmt, though specificity for Icmt is lacking 48 . It is worth noting that there were initial reservations that specific Icmt inhibitors might be toxic to cells because they would affect all prenylated proteins; these concerns have been significantly mitigated by recent work showing that although the localization of farnesylated proteins is strongly affected when methylation is blocked, the localization of geranylgeranylated proteins (the main class of prenylated proteins) is relatively unaffected 49 . Efforts to identify specific Icmt inhibitors are currently underway.…”
Section: Enzymatic Processing Of Prenylated Proteinsmentioning
confidence: 99%